2019
DOI: 10.17554/j.issn.2311-5106.2019.06.281-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment Options for Partial Rotator Cuff Tears: A Review of the Literature

Abstract: Partial-thickness rotator cuff tears (PTRCT) can be articularsided, bursal-sided or intratendinous. New research suggests that a considerable proportion (up to 30%) of cuff thickness on the articular side is taken up histologically by the superior joint capsule conjoined to the rotator cuff tissue. This means that newer reviews of the surgical options may be required to complement the Ellman classification which grades lesions as grade 1 (less than 25% of tendon thickness involved), grade 2 (25-50%) or grade 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Patients with a bursal side tear should be closely monitored for their response to nonoperative management, with consideration given to those with tears >50% of the thickness for early surgical intervention. 5 Tear size and depth, patient age and activity level, and cause of the tear also have to be considered. 6 , 7 The recommended treatment for bursal side tears includes debridement with or without acromioplasty for grade I tears (low grade) and rotator cuff–tendon repair for grade II and III tears (high grade).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a bursal side tear should be closely monitored for their response to nonoperative management, with consideration given to those with tears >50% of the thickness for early surgical intervention. 5 Tear size and depth, patient age and activity level, and cause of the tear also have to be considered. 6 , 7 The recommended treatment for bursal side tears includes debridement with or without acromioplasty for grade I tears (low grade) and rotator cuff–tendon repair for grade II and III tears (high grade).…”
Section: Introductionmentioning
confidence: 99%
“…Provided the guidelines initially proposed by Ellman are followed, the outcome of surgical repair of partial-thickness rotator cuff tears remains excellent, consistent with the outcome expected of surgical repair of small rotator cuff tears in general. For individuals who are not overhead throwing athletes, studies have shown low complication rates and good to excellent results in most cases ( 9 , 17 , 18 , 20 ).…”
mentioning
confidence: 99%